A prospective randomized half-body study: 308 nm LED light vs. 308 nm excimer laser for localized psoriasis - Yu, Yingyuan; Lu, Jiajing; Zhang, Yi; Shi, Yuling (Frontiers in Medicine, 2023)
Background: Psoriasis is a chronic skin disease affecting approximately 3.2% of the population. The 308-nm light emitting diode (LED) is a novel, portable, and cost-effective light source, may have potential in the treatment of localized psoriasis patients in a home setting. Objective: To compare the clinical and dermoscopic responses in localized psoriatic patients undergoing localized phototherapy with 308-nm LED light and excimer laser. Methods: Twenty-two patients with mild-to-moderate psoriasis and symmetrical skin lesions were included in this prospective, randomized, left-to-right body trial. The target lesions were randomly treated with either LED light or excimer laser twice a week for 12 weeks. The responses were evaluated by the Local Psoriasis Severity Index (LPSI) scores, and dermoscopic features of the target lesions were examined and analyzed. Results: Out of the 22 included psoriasis patients, 10 successfully completed the 12-week study. Both treatment sides showed similar clinical improvement in terms of clinical response, as evidenced by a LPSI 50 rate of 70% on the LED side and 80% on the excimer side, p > 0.05. Furthermore, the dermoscopic features also exhibited comparable improvement. Conclusion: The efficacy and safety of 308-nm LED light therapy are comparable to 308-nm excimer laser therapy. Moreover, given the portability and cost-effectiveness of 308-nm LED light, it holds great promise as a home phototherapy in the treatment of psoriasis.